MAINAN SEBAGAI MEDIA TRANSFER NILAI-NILAI ETIKA DI MASYARAKAT BADUY DALAM - Mohamad Zaini Alif (Universitas PGRI Adi Buana Surabaya, 2020)
Baduy Dalam society is people who live in the area located in the Village of Kanekes, South Banten, Banten Province, Indonesia. In their daily activities there are children's activities called unknown play which they call pagawean barudak. The use of playing tools using materials, and methods that are within the scope of its culture, as a form of transfer of pikukuh values ​​or ancestral teachings that contain customary rules in Baduy Dalam. The forms that exist in the pagawean barudak are a medium for transferring ethical values ​​to the teaching of customs and culture. How communication play equipment is used, ways and systems that do it. their effectiveness in using media as a medium for teaching rules, prohibitions and values ​​is their strength in their cultural system. play in the Baduy Dalam community as a scaffolding media that guides childhood by changing the level of teaching guidance and transfer of values. Pagawean barudak or playing in Baduy society emphasizes collaboration, harmony, social interaction, and socio-cultural activities, with the final point of achievement depending on which skills are considered important in that culture.